DIAGNOSIS DAN TATA LAKSANA NEUROMYELITIS OPTICA SPECTRUM DISORDER (NMOSD) - Estiasari, Riwanti; Chandra, Fitria; Remana Sitinjak, Monalisa; Susanto, Arief; Maharani, Kartika; Imran, Darma (PERDOSNI, 2024)
Neuromyelitis optica spectrum disorders (NMOSD) is an autoantibody mediated chronic inflammatory disease that predominantly affects optic nerves and spinal cord. NMOSD patients could experience visual disturbances, sensorimotor disorders, or autonomic disorders aligned with the pathological lesion involvement. Diagnostic criteria of the International Panel for NMO Diagnosis (IPND) 2015 are utilized to establish NMOSD diagnosis. Management of NMOSD encompasses initial and maintenance treatments that aim to prevent disease progression.